Dynamic force spectroscopy on multiple bonds: experiments and model - Erdmann, Thorsten; Schwarz, Ulrich S. (epl, 2008)
We probe the dynamic strength of multiple biotin-streptavidin adhesion bonds under linear loading using the biomembrane force probe setup for dynamic force spectroscopy. Measured rupture force histograms are compared to results from a master equation model for the stochastic dynamics of bond rupture under load. This allows us to extract the distribution of the number of initially closed bonds. We also extract the molecular parameters of the adhesion bonds, in good agreement with earlier results from single-bond experiments. Our analysis shows that the peaks in the measured histograms are not simple multiples of the single-bond values, but follow from a superposition procedure which generates different peak positions.